Fatal complications in juvenile diabetes mellitus Letale Komplikationen bei juvenilem Diabetes mellitus - Feld, K.; Kamphausen, T.; Jübner, M.; Rothschild, M. A.; Banaschak, S. (Rechtsmedizin, 2019)
Diabetes mellitus is one of the most common chronic diseases in childhood and adolescence, whereby a clear increase in the prevalence of type 2 diabetes mellitus can be observed in this age group. This disease can lead not only to long-term damage but also to sometimes fatal complications, especially in puberty. This article presents two autopsy cases with such fatal complications. In one case the underlying disease was type 1 diabetes mellitus and in the second case type 2 diabetes mellitus. Following the autopsy in both cases post-mortem biochemical and toxicological investigations could be carried out and by the use of the Traub formula the cause of death could be established as a diabetic coma (hyperosmolar and ketoacidotic) due to insufficient administration of insulin.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Acute pancreatitis; Diabetic coma; Insulin pump; Ketoacidosis; Traub formula